2018
DOI: 10.1126/science.aar7366
|View full text |Cite
|
Sign up to set email alerts
|

RNA buffers the phase separation behavior of prion-like RNA binding proteins

Abstract: Prion-like RNA binding proteins (RBPs) such as TDP43 and FUS are largely soluble in the nucleus but form solid pathological aggregates when mislocalized to the cytoplasm. What keeps these proteins soluble in the nucleus and promotes aggregation in the cytoplasm is still unknown. We report here that RNA critically regulates the phase behavior of prion-like RBPs. Low RNA/protein ratios promote phase separation into liquid droplets, whereas high ratios prevent droplet formation in vitro. Reduction of nuclear RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

130
1,121
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 912 publications
(1,252 citation statements)
references
References 54 publications
(36 reference statements)
130
1,121
0
1
Order By: Relevance
“…Specifically, at 5:1 rPrP 90-231 :aptamer stoichiometry, the number of droplets/0.1 mm 2 was 98.33 ± 9.46 for A1 and 73.66 ± 14.97 for A2, respectively, versus 12.33 ± 5.31 for rPrP 90-231 in buffer without aptamers ( Figure 8D). 21 Therefore, our data agree with data for other NA-binding proteins that undergo LLPS. It was previously shown that LLPS is highly dependent on the protein:NA molar ratio, where lower ratios of specific NAs promote phase separation.…”
Section: Aptamers Modulate Rprp 90-231 Llpssupporting
confidence: 89%
See 3 more Smart Citations
“…Specifically, at 5:1 rPrP 90-231 :aptamer stoichiometry, the number of droplets/0.1 mm 2 was 98.33 ± 9.46 for A1 and 73.66 ± 14.97 for A2, respectively, versus 12.33 ± 5.31 for rPrP 90-231 in buffer without aptamers ( Figure 8D). 21 Therefore, our data agree with data for other NA-binding proteins that undergo LLPS. It was previously shown that LLPS is highly dependent on the protein:NA molar ratio, where lower ratios of specific NAs promote phase separation.…”
Section: Aptamers Modulate Rprp 90-231 Llpssupporting
confidence: 89%
“…21,44 Relevantly, A1 and A2 kept rPrP 90-231 condensates in a dynamic state, preventing transition to solid-like structures in the timeframe examined. 21,44 Relevantly, A1 and A2 kept rPrP 90-231 condensates in a dynamic state, preventing transition to solid-like structures in the timeframe examined.…”
Section: Aged Rprp 90-231 :A1_mut Droplets Evolve To Amyloid-like Fmentioning
confidence: 96%
See 2 more Smart Citations
“…

Coacervate microdroplets produced by liquid-liquid phase separation have been used as synthetic protocells that mimic the dynamical organization of membrane-free organelles in living systems.A chieving spatiotemporal control over droplet condensation and disassembly remains challenging. [3,4] Microdroplets produced in vitro by associative (coacervates) or segregative (aqueous two-phase systems) liquid-liquid phase separation have recently been used as synthetic models of dynamic protocells. The droplets disassemble and reassemble under UV and blue light, respectively,d ue to azobenzene trans/cis photoisomerisation.

…”
mentioning
confidence: 99%